Federal government agricultural financing and economic growth in Nigeria - Rasaki Olufemi Kareem; Rukayat Adebunmi Arije; Zakariah Olayiwola Amoo; Hassan Yusuf Avovome (Economic Review: Journal of Economics and Business, 2022)
This paper analyzed the impact of federal government agricultural financing on economic growth in Nigeria. The study utilized the time series data which was extracted from the Central Bank of Nigeria statistical bulletin. The properties of the variables were tested using the Augmented Dickey- Fuller unit root test. A Single equation cointegration test confirmed no cointegration and a short-run vector autoregressive model was used to analyze the data, after which the diagnostic test was carried out to confirm the normality of the series. The study revealed that federal government agricultural financing has a negative contribution to economic growth in Nigeria and was statistically insignificant. Agricultural Credit Guarantee Scheme Funds had a positive but not statistically significant contribution to economic growth and there was no causal relationship among the variables. The study concluded that federal government agricultural financing has no significant impact on economic growth in Nigeria. Therefore, the study recommended that federal government should increase funding to the agricultural sector to be able to impact positively on the economic growth of Nigeria.
Keywords: N2; Q; E6; C32; 330; agricultural sector; agriculturalfinance; unit root test; economic growth